Considerations on the management of gastroesophageal varices resulting from portal hypertension (Research, Society and Development, 2024)
Introduction: Liver cirrhosis is currently the leading cause of portal hypertension, which is a clinical condition with many pathophysiological consequences. In this sense, the approach to gastroesophageal varices resulting from this condition represents a clinical entity of great relevance to the medical scenario. Objectives: The objetive of this study was to evaluate the clinical, epidemiological and pathophysiological aspects of esophageal varices resulting from portal hypertension, building knowledge based on case reports and knowledge based on the literature. Materials and Methods: This is an integrative literature review on the general clinical characteristics of esophageal varices. The PICO strategy was used to develop the guiding question. In addition, the descriptors "Esophageal Varices"; "Portal Hypertension"; "Propaedeutics" were cross-referenced in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (SCIELO), Ebscohost, Google Scholar and Virtual Health Library (VHL) databases. Results and Discussion: A significant proportion of the articles showed that variceal upper gastrointestinal bleeding results from the alterations caused by portal hypertension and that it must be managed incisively in order to improve the patient's prognosis. Conclusion: It was possible to see that the management of digestive hemorrhage has to be started as early as possible, with the need to stabilize the patient with active bleeding. In addition, the use of vasoactive drugs and prophylactic antibiotic therapy are indicated in association with endoscopic treatment, which should be the first line of choice.